2019
DOI: 10.1002/cne.24753
|View full text |Cite
|
Sign up to set email alerts
|

Dual recombinase fate mapping reveals a transient cholinergic phenotype in multiple populations of developing glutamatergic neurons

Abstract: Cholinergic transmission shapes the maturation of glutamatergic circuits, yet the developmental sources of acetylcholine have not been systematically explored. Here, we have used Cre‐recombinase‐mediated genetic labeling to identify and map both mature and developing CNS neurons that express choline acetyltransferase (ChAT). Correction of a significant problem with a widely used ChatCre transgenic line ensures that this map does not contain expression artifacts. ChatCre marks all known cholinergic systems in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 115 publications
(137 reference statements)
2
21
0
Order By: Relevance
“…Therefore, we pursued a second intersectional cross using Chat IRES-Cre and Cdx2::FLPo crossed to the intersectional Ai65 tdTomato reporter (hereafter called Chat Cdx2 neurons). Chat IRES-Cre/+ labels all cholinergic cells and cells with transient Chat expression (Rossi et al, 2011; Nasirova et al, 2020) while the Cdx2::FLPo labels all cells caudal to the mid-cervical area of the spinal cord (Bourane et al, 2015). We found that in the spinal cord, labeling of MNs was much more robust with 92% of the MNs being labeled (n=1) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, we pursued a second intersectional cross using Chat IRES-Cre and Cdx2::FLPo crossed to the intersectional Ai65 tdTomato reporter (hereafter called Chat Cdx2 neurons). Chat IRES-Cre/+ labels all cholinergic cells and cells with transient Chat expression (Rossi et al, 2011; Nasirova et al, 2020) while the Cdx2::FLPo labels all cells caudal to the mid-cervical area of the spinal cord (Bourane et al, 2015). We found that in the spinal cord, labeling of MNs was much more robust with 92% of the MNs being labeled (n=1) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The lack of robust MN labeling in the Chat Hoxa4 mice might be due to the dorsal-enriched expression of Hoxa4::Cre that would miss ventrally generated neuronal populations (Yuengert et al, 2015). In contrast, the Chat Cdx2 mice labeled almost all the MNs (92%), but also labeled many other neurons with potentially ascending projections in the spinal cord likely due to transient Chat expression (Nasirova et al, 2020). In both mice, other cholinergic neurons in the spinal cord (SPN, V 0c ) were labeled, although these should not have any ascending projections (Zagoraiou et al, 2009; Deuchars and Lall, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations